How do firms cope with losses from extreme weather events? - Benincasa, Emanuela; Betz, Frank; Gattini, Luca (Journal of Corporate Finance, 2024)
We document the investment and financing decisions of firms that experience monetary losses due to extreme weather events. Our sample covers firms operating in 41 economies, mainly emerging and developing markets. Consistent with the need to either replenish damaged capital or to adapt to climate change, firms with weather-related losses are more likely to invest in long-term assets and integrate climate-friendly measures into their production processes. On average, these firms have higher needs for bank credit and are less likely to be discouraged from applying for a loan. Small firms appear particularly vulnerable to physical climate risk as they show a lower propensity to invest, while they are in greater need for bank credit. Firms with losses from extreme weather events are more leveraged, which suggests that climate change has the potential to erode balance sheets over time.